Specific Marking of hESCs-Derived Hematopoietic Lineage by WAS-Promoter Driven Lentiviral Vectors - Muñoz, Pilar; Toscano, Miguel G.; Real, Pedro J.; Benabdellah, Karim; Cobo, Marién; Bueno, Clara; Ramos-Mejía, Verónica; Menendez, Pablo; Anderson, Per; Martín, Francisco (PLOS ONE, 2012)
Genetic manipulation of human embryonic stem cells (hESCs) is instrumental for tracing lineage commitment and to studying human development. Here we used hematopoietic-specific Wiskott-Aldrich syndrome gene (WAS)-promoter driven lentiviral vectors (LVs) to achieve highly specific gene expression in hESCs-derived hematopoietic cells. We first demonstrated that endogenous WAS gene was not expressed in undifferentiated hESCs but was evident in hemogenic progenitors (CD45−CD31+CD34+) and hematopoietic cells (CD45+). Accordingly, WAS-promoter driven LVs were unable to express the eGFP transgene in undifferentiated hESCs. eGFP+ cells only appeared after embryoid body (EB) hematopoietic differentiation. The phenotypic analysis of the eGFP+ cells showed marking of different subpopulations at different days of differentiation. At days 10–15, AWE LVs tag hemogenic and hematopoietic progenitors cells (CD45−CD31+CD34dim and CD45+CD31+CD34dim) emerging from hESCs and at day 22 its expression became restricted to mature hematopoietic cells (CD45+CD33+). Surprisingly, at day 10 of differentiation, the AWE vector also marked CD45−CD31low/−CD34− cells, a population that disappeared at later stages of differentiation. We showed that the eGFP+CD45−CD31+ population generate 5 times more CD45+ cells than the eGFP−CD45−CD31+ indicating that the AWE vector was identifying a subpopulation inside the CD45−CD31+ cells with higher hemogenic capacity. We also showed generation of CD45+ cells from the eGFP+CD45−CD31low/−CD34− population but not from the eGFP−CD45−CD31low/−CD34− cells. This is, to our knowledge, the first report of a gene transfer vector which specifically labels hemogenic progenitors and hematopoietic cells emerging from hESCs. We propose the use of WAS-promoter driven LVs as a novel tool to studying human hematopoietic development.